Single-Spore Culture of Racocetra crispa Using a Legume Tree Species - Faisal Danu Tuheteru; Deli; Husna Husna; Asrianti Arif; Wiwin Rahmawati Nurdin (Asosiasi Mikoriza Indonesia, 2026)
The propagation of Racocetra crispa using tree-like legume host plants has not yet been widely undertaken. This study aims to investigate the sporulation of R. crispa in single-spore cultures using legume tree host plants, namely sengon (Paraserianthes falcataria), albizia (Albizia saponaria), johar (Cassia siamea), cajanus (Cajanus cajan), and lamtoro (Leucaena leucocephala). The study was conducted at the Greenhouse of the Indonesian Mycorrhiza Association (AMI) Southeast Sulawesi Branch and the Forestry Department Laboratory of Halu Oleo University from November 2025 to February 2026. The study employed a completely randomised design (CRD) with 5 treatments and 3 replicates. The variables observed included culture success, AMF colonisation of the roots, and the number of spores formed at 3 months, 5 months, and after drying 10 g of medium. The results of the study showed that the A. saponaria host plant treatment yielded the best results, with a culture success rate of 86.67%, the highest AMF colonisation of 35.83%, and the highest number of spores at 5 months and after drying 10g of medium. Conversely, L. leucocephala showed the lowest results, with a culture success rate and spore count of 0%. The best host plant for the propagation of Racocetra crispa is A.saponaria.